A rise in T3/T4 ratio reduces the growth of prostate tumors in a murine model. Issue 3 (December 2020) - Sánchez-Tusie, Ana; Montes de Oca, Carlos; Rodríguez-Castelán, Julia; Delgado-González, Evangelina; Ortiz, Zamira; Álvarez, Lourdes; Zarco, Carlos; Aceves, Carmen; Anguiano, Brenda
Abstract : Thyroxine (T4 ) promotes cell proliferation and tumor growth in prostate cancer models, but it is unknown if the increase in the triiodothyronine (T3 )/T4 ratio could attenuate prostate tumor development. We assessed T3 effects on thyroid response, histology, proliferation, and apoptosis in the prostate of wild-type (WT) and TRAMP (transgenic adenocarcinoma of the mouse prostate) mice. Physiological doses of T3 were administered in the drinking water (2.5, 5 and 15 µg/100 g body weight) for 6 weeks. None of the doses modified the body weight or serum levels of testosterone, but all of them reduced serum T4 levels by 50%, and the highest dose increased the T3 /T4 ratio in TRAMP. In WT, the highest dose of T3 decreased cyclin D1 levels (immunohistochemistry) but did not modify prostate weight or alter the epithelial morphology. In TRAMP, this dose reduced tumor growth by antiproliferative mechanisms independent of apoptosis, but it did not modify the intraluminal or fibromuscular invasion of tumors. In vitro, in the LNCaP prostate cancer cell line, we found that both T3 and T4 increased the number of viable cells (Trypan blue assay), and only T4 response was fully blocked in the presence of an integrin-binding inhibitor peptide (RGD, arginine-glycine-aspartate). In summary, our data show that the prostate was highly sensitive to physiological T3 doses and suggest that in vivo, an increase in the T3 /T4 ratio could be associated with the reduced weight of prostate tumors. Longitudinal studies are required to understand the role of thyroid hormones in prostate cancer progression.